Experimental Results and Modeling of Magnetic Data for the Gallium Oxide-Hematite Mixed-Oxide Nanoparticles - Sorescu, Monica; Tolea, Felicia; Sofronie, Mihaela (Transactions on Engineering and Computing Sciences, 2025)
The xGa2O3*(1-x)Fe2O3 (x=0.5) was prepared by mechanochemical activation using high energy ball milling for times of 0, 2, 4, 8, and 12 hours. The magnetic properties were studied by hysteresis loop measurements with an applied magnetic field of 5 T at temperatures of 5 and 300 K. Zero-field-cooling-field-cooling results were obtained in a magnetic field of 200 Oe in the temperature range 5-300 K. The magnetization and average coercive field were investigated as functions of ball milling time and temperature. They were related to changes in the average grain size, induced stresses and defects, variations in exchange coupling and magnetic ordering. ZFC did not exhibit a sharp edge, so we do not witness superparamagnetism with a well-defined blocking temperature. The Morin transition of hematite occurred over broad temperature ranges and was monitored as a function of ball milling time. The Dzyaloshinskii-Moriya antisymmetric exchange interaction explained the gradual increase in the magnetization with ball milling time.